AN ANALYSIS OF SELECTED ELEVENTH GRADE ENGLISH TEXTBOOKS - Rizky Akbar (Journal of English and Education, 2016)
Textbooks play a pivotal role in language classrooms in all types of educational institutions. However, textbook selection and evaluation is often given little time or attention despite its central role in most language courses. This study aimed at determining the extent to whichtwo selected eleventh grade English textbooks are appropriate in terms of content based on BSNP framework for textbook evaluation. Using descriptive qualitative method, this study attempted to find out the appropriateness of the content of the textbooks. A checklist adapted from BSNP (2014) framework for textbook evaluation was made, focused on the areas of relevance of materials with competency standards and basic competencies, materials accuracy, and supporting learning materials. The findings show that both textbooks were appropriate in terms of content based on BSNP framework for textbook evaluation.